First-principles explorations of mechanical, electronic and thermodynamic properties of (o, h)-AlCu3 compounds. (September 2021) - Cao, Yong; Wang, Liqiong; Zhang, Cong; Xu, Yang; Luo, Penghui; Tian, Chang; Tian, Meiling; You, Yuanqi; Zhou, Shenggang
Abstract: In this study, we used the first-principles calculation method based on density functional theory to study systematically the mechanical, electronic and thermodynamic properties of o-AlCu3 and h-AlCu3 compounds. The calculation results of formation enthalpies showed that these two compounds are thermodynamically stable, and o-AlCu3 has higher thermodynamic stability. The calculation results of the elastic constants of single-crystal and polycrystalline showed that both o-AlCu3 and h-AlCu3 have mechanical stability, and they are all ductile materials, the order of ductile is: h-AlCu3 > o-AlCu3 . The discussion of anisotropic elasticity showed that both o-AlCu3 and h-AlCu3 are anisotropic, and the order of anisotropy is: o-AlCu3 > h-AlCu3 . The research of electronic properties showed that both o-AlCu3 and h-AlCu3 are metallic, and the Al-Cu chemical bond strength of o-AlCu3 is higher than that of h-AlCu3 . Finally, the quasi-harmonic Debye model is used to calculate and analyze the thermodynamic properties, such as the heat capacity, thermal expansion coefficient, Debye temperature and Grüneisen parameter, in the pressure range of 0–40 GPa and the temperature range of 0–800 K. To the best of our knowledge, this work represents the first theoretical prediction on o-AlCu3 and h-AlCu3 compounds and needs to be verified by experiments.